Geologia, petrografia e geoquímica e suscetibilidade magnética do Granito Paleoproterozoico São João, Sudeste do Cráton Amazônico, Província Carajás - LIMA, Paulo Henrique Araújo (Universidade Federal do Pará, 2015)
The São João granite (SJG) is an anorogenic batholith of circular form, with an area of approximately 160 km2, which cuts Archean units of the Rio Maria Granite-Greenstone Terrain, southeastern Amazonian Craton. It consists of four distinct petrographic facies: biotite-amphibole monzogranite (BAMG), biotite-amphibole syenogranite (BASG), amphibole-biotite monzogranite to syenogranite (ABMSG) and biotite monzogranite to syenogranite (BMSG). The SJG has a metaluminous to weakly peraluminous nature, FeOt/(FeOt+MgO) ratios varying from 0.94 to 0.99 and K2O/Na2O from 1 to 2, shows geochemical affinities with the intraplate granites, A-type granites of A2 subtype and ferrous granites, suggesting a crustal source for its origin. The SJG has higher contents of LREE compared to HREE and a sub-horizontal pattern for the latter. The negative anomalies of Eu rising from less evolved towards more evolved rocks (BAMG → BASG→ ABMSG→ BMSG). Magnetic susceptibility data (MS) allowed the identification of six populations with different magnetic characteristics, where the highest values of MS relate to the less evolved facies and the lowest to the more evolved facies. The comparison between SJG and the granite suites of the Carajás Province shows that it displays strong geological, petrographic, geochemical and MS similarities with the granites of the Serra dos Carajás suite, and may be preliminarily included in the same.